Small-Bore Needle Arthroscopic Extensor Carpi Radialis Brevis Release Results in Improved Outcomes at One Year Postoperatively - Wyatt Daniel Vander Voort, M.D; Maarouf Saad, M.D; David Falgout, M.D; Theodore A. Blaine, M.D; Hafiz F. Kassam, M.D (Elsevier, 2023)
Purpose: To evaluate outcomes of patients who underwent small-bore needle arthroscopic extensor carpi radialis brevis (ECRB) release for the management of recalcitrant lateral epicondylitis. Methods: Patients who underwent elbow evaluation and ECRB release using a small-bore needle arthroscopy system were included in this study Thirteen patients were included. Quick Disabilities of the Arm Shoulder and Hand and Single Assessment Numerical Evaluation scores, as well as overall satisfaction scores, were collected. A 2-tailed paired t-test was conducted to assess the statistical significance of the differences observed between preoperative and 1-year postoperative scores with significance set at P < .05. Results: There was a statistically significant improvement in both outcome measures (P < .001) and a 92.3% satisfaction rate with no significant complications at a minimum 1-year follow-up. Conclusions: Patients with recalcitrant lateral epicondylitis treated with ECRB release using needle arthroscopy demonstrated significantly improved Quick Disabilities of the Arm Shoulder and Hand and Single Assessment Numerical Evaluation scores postoperatively, without complications. Level of Evidence: IV, retrospective case series.